Relationships with the Chancellor and How They Affect Cal Poly, 1962 - Julian A. McPhee::::::::: (1962)
Documentation of the Cal Poly president, Julian McPhee, discussing the relationship between colleges in the California State Colleges (CSC) system and the CSC Chancellor, during a time of transition (1962) within the CSC administration. 1962 marked the year Glenn Dumke succeeded Buell Gallagher as CSC Chancellor, a position he would keep until 1982. [00:00:22] Introductory speaker (Phil?) presents Dr. McPhee [00:01:17] Applause, McPhee thanks staff [00:01:46] McPhee explains why he enjoys speaking to the staff in an informal session [00:03:25] McPhee discusses items he will speak about, including relationships with Chancellor Dumke, '63-64 budget, long-range planning [00:04:22] Difficulty in appointing a chancellor [00:05:00] Chancellor encountering problems upon starting [00:06:28] Communists on the campus [00:07:12] Various conflicting political leanings in the state college system [00:08:11] Pressure on the trustees by various interest groups [00:09:45] Predictions for enrollment growth in state college system [00:11:31] McPhee talks about studies made to determine the cost of schooling compared to admission numbers [00:13:15] Studies requested by the legislature [00:16:30] McPhee talks about the problems with writing a budget without specifically paying attention to individual schools [00:18:39] Chancellor says that half of the trustees are opposed to residence halls [00:19:15] Private colleges are opposed to state colleges having residence halls [00:22:25] McPhee remembers various Board of Education members from the 1930s [00:24:53] McPhee will meet with state college representatives and trustees in the coming months [00:25:57] Cal Poly Long-Range planning [00:27:07] McPhee talks about meeting with department heads and progress toward long-term goals [00:28:19] McPhee stresses the importance of the Long-Range planning program [00:31:04] Most important thing during '61-62 year was providing the best education possible [00:32:00] Auxiliary services like buses, cafeterias, etc [00:34:00] McPhee continues reading a speech about self-reflection on the part of the teachers and analysis to create a good learning experience [00:37:28] Cal Poly's effectiveness comes from good courses and good teachers [00:38:51] McPhee thanked; end of recording